Brand equity and customer citizenship behavior among students of selected universities within Mount Kenya region (African Journal of Science, Technology and Social Sciences, 2022)
The growing number of higher learning institutions in Kenya and around the world has emphasized the importance of brand equity in customer decision-making. Despite the role of brand equity, enrollment in public universities has been declining in the past three years. The study was conducted to establish effect of brand equity on customer citizenship behavior among students of selected universities within Mount Kenya region. The study was anchored on Keller brand theory. A descriptive research survey was utilized and target population was 600 4 th year students of selected universities within Mount Kenya region. A sample size of 240 students was selected simple random sampling. Primary data was collected using both closed and open-ended questionnaires. Data analysis was done using descriptive and inferential statistics including correlation and regression analysis. Results indicated an R squared of 0.565. This denoted that brand equity explains 57% of the variations in the customer citizenship behavior. Findings also indicated that brand equity had a positive and significant effect on customer citizenship behavior (β=0.912, p<0.05). This suggested that a marginal increase in brand equity will lead to 0.912 increase in customer citizenship behavior. The study concluded that brand equity significantly contributes to improved customer citizenship behavior (57%). The study recommended that universities management should consider engaging in strong advertising and marketing campaigns so as to create more brand awareness and hence build customer citizenship behaviour. The university administrators should make sure the brand image conjures cleanliness. They should also create a positive and inviting environment. The government and ministry of education policymakers should also promote brand equity in Kenyan universities.
Keywords: Brand Equity; Customer Citizenship Behaviour; University students